Inhibition of p38 MAPK activation protects cardiac mitochondria from ischemia/reperfusion injury - Sarawut Kumphune (2018)
© 2015 Informa Healthcare USA, Inc. Context: Cardiac cell death and fatal arrhythmias during myocardial ischemia/reperfusion (I/R) can be reduced by p38 MAPK inhibition. However, the effects of p38 MAPK inhibition on cardiac mitochondria have not been investigated. Objective: We tested the hypothesis that p38 MAPK inhibition at different times during I/R protects cardiac mitochondrial functions. Materials and methods: Adult Wistar rats were subjected to 30 min of left anterior descending coronary artery (LAD) occlusion, followed by 120 min of reperfusion. A 2 mg/kg bolus infusion of p38 MAPK inhibitor, SB203580, was given before or during ischemia, or at reperfusion. Mitochondrial function and ultrastructure were assessed and Western blots were performed. Results: Administration of SB203580 at any time point of I/R significantly attenuated the mitochondrial ultrastructure change, mitochondrial swelling, by increasing the absorbance at 540 nm (I/R control 0.42 ± 0.03; pretreatment 0.58 ± 0.04; during ischemia 0.49 ± 0.02; at reperfusion 0.51 ± 0.02, p<0.05), similar to reactive oxygen species (ROS) generation (I/R control 1300 ± 48; pretreatment 1150 ± 30; during ischemia 1000 ± 50; at reperfusion 1050 ± 55, p<0.05). Only SB203580 given before or during ischemia attenuated mitochondrial membrane depolarization (I/R control 0.78 ± 0.04; pretreatment 1.02 ± 0.03; during ischemia 1.05 ± 0.12, p<0.05). In addition, pre-treatment of SB203580 significantly reduced the phosphorylation of p53, CREB, Bax, cytochrome c, and cleaved caspase 3. Discussion and conclusion: The results from this study showed for the first time that p38 MAPK inhibition protects mitochondria from I/R injury.